Evaluation of the Educational Program in Enhancing the Understanding of Students at TPQ Nurul Qur’an, Bukek Village, Tlanakan District, Pamekasan Regency - Masruroh Masruroh; Rusdiana Navlia (Kasyafa: Jurnal Pendidikan Agama Islam, 2026)
This research discusses the implementation of educational programs at TPQ Nurul Qur'an with a focus on the ustadzah's habit of inviting students to pray before and after learning, the effectiveness of the program, teaching methods, and the obstacles faced during the Al-Qur'an learning process. The research found that the ustadzah displays consistency in inviting students to pray as a manifestation of requests for ease, blessings and gratitude in learning to recite the Koran. The educational program at TPQ Nurul Qur'an runs smoothly and is structured with the main aim of teaching students from Iqra' to fluency in reading the Al-Qur'an with correct tajwid, as well as basic Islamic education such as memorizing short letters and practicing worship. The teaching method used by the ustadzah applies a classical and individual approach so that the material can be easily understood, with the habit of studying juz and an intensive understanding of the laws of recitation. The problem faced mainly concerns the students' ability to read the Koran fluently with correct tajwid and makhraj letters. However, learning at TPQ Nurul Qur'an has succeeded in forming good habits and forming Islamic character among the students. The implications of this research highlight the role of prayer as an important factor in forming attitudes and learning excellence, as well as the need to improve the quality of teaching and provide motivation to students to overcome obstacles to reading the Al-Qur'an optimally.